The effect of Hordeum vulgare on the monoaminergic system modulating neural-thyroid dysfunction in hypothyroid female rats - Wahman, Lobna F.; Abd-Rabo, Marwa M.; Youseef, Magda H. M.; Abdel-Hameed, Usama K. (Cellular and Molecular Biology, 2019)
Thyroid hormones regulate the development and maturation of the brain by maintaining levels of neurotransmitters and their related metabolites. The present work emphasizes the neural dysfunction in the brain caused by hypothyroidism and the potential role of Hordeum vulgare (water soluble barley, (B)) in ameliorating these effects. The study was conducted on euothyroid and hypothyroid adult female rats. The induction of hypothyroidism was conducted by oral-administration of neo-mercazole (5.0 mg.kg-1) daily for thirty days prior the study and terminated at the end of the study. The groups were assigned as; euthyroid (EU) and hypothyroid (H) groups and other two groups were treated with 100 mg.kg-1 water soluble barley; daily for one month and assigned as (EU+B) and (H+B) groups. Compared with EU and EU+B groups, a reduction in fT4, and ERK1/2 levels and elevation in TSH in brain tissue, Moreover, a significant elevation in 8-OH deoxyguanosine and caspase-3 levels, confirmed with increase percentage DNA-damage in the brain and thyroid tissues in hypothyroid control rats. Furthermore, a significant decrease in all monoamines levels in different brain areas and downregulation of dopamine and 5-hydroxytreptamin receptors transcription, with a significant increase in excitatory amino acids and no significant change in the levels inhibitory amino acids were recorded in control hypothyroid group. Treatment of hypothyroid group with Hordeum vulgare improved the above-mentioned adverse impact by ameliorating the thyroid hormone levels with depleting the DNA-degradation and elaborating the levels of neurotransmitters with related receptors and amino acids in brain areas. Water soluble Hordeum vulgare as a phytonutrient, is safe and efficient agent in ameliorating the neural dysfunction resulting from hypothyroidism status in adult female rats.